The revival of cancer vaccines - The eminent need to activate humoral immunity - Elisabeth J. M. Huijbers; Arjan W. Griffioen (Taylor & Francis Group, 2017)
In light of the increasing number of approved monoclonal antibodies for the treatment of cancer, it seems peculiar that the development of antibody inducing vaccines gets so little attention. In our view there is a tremendous opportunity in the development of cancer vaccines inducing humoral immune responses, involving a couple of major advantages. Firstly, the effectivity of a polyclonal antibody response is expected to exceed the one of monoclonal antibodies. This is supported by preclinical data that show pronounced anti-tumor responses and early clinical trials in which benefit is observed in patients with advanced cancer. Secondly, vaccination strategies are expected to reduce hospital visits, resulting in enhanced quality of life. And last but not least, vaccination strategies are extremely cost effective, alleviating the socioeconomic problems of prohibitively high drug costs. To reach further clinical success, efforts should focus on target identification, optimization of vaccination strategies and adjuvant development.